Digressão do ideal democrático: a representatividade política como instrumento de controle social - Figueiredo, Camile Araújo (2016)
The democratic regime it is a way throuth which the people in the exercise of their political rights would be as an active part in political issues that drive the social system. For that purpose, it was established the "State Parties", that means the prevalence of the party system as the best expression of the "ideal" democratic. Faced this understanding, the political parties it is one of the instruments through which voters would have their interests represented. Influenced by the economic system, the party acting has ceased to be the sole purpose of the realization of the collective interest, going to seek individual benefits conferred by drivers of the economy – the greatest businessmen. Considering the idea of correlation between economic and political system, then, it goes to the philosophical analysis of the subject’s formation – as an individual and as a collective in the perspective of Michel Foucault. Thus, there is the normative institution as a maker and guarantor of this political and economical scenario, through the creation of a docile subject as an individual and the creation of an obedient community. Due to the pursuit of the idealized form of political representation, it was assigned to the representative regime a "crisis". Thus, this paper aims to discuss the conceptualism that involves the "ideal" democratic representation to demystify the existence of such "representative crisis", once the reasons that feed the sense of crisis are inherent of the mencioned political and democratic scenario.